Wage Bargaining and Induced Technical Change in a Linear Economy: Model and Application to the US (1963-2003) - Daniele Tavani (Economics and Econometrics Research Institute (EERI), 2009)
In a simple one-sector, two-class, fixed-proportions economy, wages are set through axiomatic bargaining a`la Nash (1950). As for choice of technology, firms choose the direction of factor augmentations to maximize the rate of unit cost reduction (Kennedy 1964, and more recently Funk 2002). The ag-gregate environment resulting by self-interested decisions made by economic agents is described by a two-dimensional dynamical system in the employment rate and output/capital ratio. The economy converges cyclically to a long-run equilibrium involving a Harrod-neutral profile of technical change, a constant rate of employment of labor, and constant input shares. The type of oscillations predicted by the model matches the available data on the United States (1963-2003). Finally, institutional change, as captured by variations in workers' bargaining power, has a positive effect on the rate of output growth but a negative effect on employment.
Keywords: E24; E25; J52; O31; 330; Bargaining; Induced Technical Change; Factor Shares; Employment